XRF, FTIR, SEM-EDS and microscopy data from the project 'Boglösa church door', RAÄ-2025-0134 - Canosa, Elyse; Berg, Helena; Jagare, Kajsa; Hansson, Ann-Sofie (Swedish National Heritage Board, 2026)
Data from the project 'Boglösa church door' (Diarienummer RAÄ-2025-0134). Data from the following analytical techniques is included: 1. Fourier transform infrared spectroscopy (FTIR); 2. X-ray fluorescence (XRF); 3. Scanning electron microscopy - energy dispersive x-ray spectroscopy (SEM-EDS); 4. UV-VIS microscopy; 5. Stereomicroscopy . Also included are instrument reports which compile the data, provide the measurement parameters and describe the samples/measurement areas for each technique.

In the spring of 2024, Acta Konservering was commissioned for the conservation of a medieval iron church door in Boglösa Church (http://kulturarvsdata.se/raa/bbr/21300000002550) . The church is originally a Romanesque church from the 12th or early 13th century. The door is in use and is located in the church entrance. The request for conservation was based on observations of problems with corrosion on the surface and cracking paint layers. During Acta's examination of the door, it was observed that the paint layers on the outside of the door were unusually intact, and that there were textile remains under the decorative elements of the door. It is very unusual for there to be preserved remains of textile and older paint on this type of door, since the iron has often been regularly surface-treated to prevent corrosion. In order to be able to carry out correct conservation measures on the door, it is important to know what color scheme the door has had, both on the metallic part of the door and the textiles. The door currently appears to be painted a dark brown, and one of the additional research questions was to identify whether this outer paint layer contains tar. There are also a number of fittings on the door that have visible corrosion products that could possibly be due to a previous tinning. In addition to this information being crucial for choosing conservation methods, it is also a unique opportunity to obtain more information about this type of object. Analysis of the paints of the door, the paint of the decorative elements and the dyes of the textiles can provide information about the original coloring of the door. Analysis of corrosion products under the paint layers on the decorative elements could also provide information about whether these have been tinned.
Keywords: Heritage science; Electron microscopy; Spectroscopy, Fourier Transform Infrared; Microscopy; x-ray fluorescence spectroscopy; Heritage conservation; Corrosion; Paint; Textiles; Dye analysis; RAÄ-2025-0134; Boglösa church; History and Archaeology; Historia och arkeologi